Physics of semiconductor devices - Sze, S. M. (Wiley-Interscience, 2007)
The book introduces the device physics and operational principles of semiconductors. It covers the basic physics of classic devices and other contemporary interest as three-dimensional MOSFETs (metal-oxide-semiconductor field-effect transistors), nonvolatile memory, modulation-doped field effect transistor, single-electron transistor, resonant-tunneling diode, insulated-gate bipolar transistor, quantum cascade laser, and semiconductor sensors.The new editon also has a sections on the physics and properties of semiconductors, device building blocks, transistors, negative-resistance and power devices, and photonic devices and sensors. Each chapter has problem set.